ANTARA DUA DUNIA: STRATEGI BERTAHAN HIDUP PENDUDUK DESA KEMADANG, KECAMATAN TANJUNGSARI, KABUPATEN GUNUNGKIDUL - , Imam Fauzi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Kemadang villages who lives in two worlds, doing activities on land and sea, because not entirely of farmers transitioning into fishing. Natural conditions in neighborhood, the land is less fertile and not productive and extreme sea conditions, so, it can not provide welfare raises various survival strategies undertaken by the villagers Kemadang living in two worlds. The development of beach tourism along the coastal area of Gunungkidul provides a more promising alternative employment for the community who live in Kemadang. This study aims to describe the issues related to agriculture and fishing activities and to find survival strategies undertaken by villagers Kemadang, Tanjungsari District, Gunungkidul in addressing the uncertainty of the income earned from agriculture and fishing activities. This study used a qualitative inductive approach. This approach allows researcher to explore any findings in the field, then described and elaborated by qualitative descriptive. Various problems faced by villagers Kemadang were identified, namely the low quality of human resources, nature, institutional, issue of over fishing, cultural and social aspects of capital shortage. The problems that come from nature, in the form of extreme natural conditions, are problems that can not be avoided by fishermen and take place over and over every year. Agriculture is not productive and often does not get the fish when fishing so that earned income is erratic. To deal with these problems, Kemadang villages have chosen survival strategies based on resource access and potential areas around it. Kemadang villages have chosen survival strategies can be grouped into two, namely the strategy of utilizing the potential coastal area and ocean as well as the strategy of utilizing the potential of the region and around the neighborhood.